Long-term survival after cord blood transplantation for acute myeloid leukemia complicated with disseminated fusariosis. Issue 2 (February 2020) - Ichikawa, Satoshi; Fukuhara, Noriko; Watanabe, Shotaro; Okitsu, Yoko; Onodera, Koichi; Onishi, Yasushi; Harigae, Hideo
Abstract: Fusariosis is a critical infectious complication that can develop in immunocompromised hosts, mainly under conditions of prolonged neutropenia, and is often disseminated and associated with a high mortality rate. Disseminated fusariosis developing during the course of hematopoietic stem cell transplantation (HSCT) is a critical condition, and there have been few reports of successful treatment of cases complicated with fusariosis before HSCT. Here, we present a case of acute myeloid leukemia (AML) with the development of fungal endophthalmitis during chemotherapy. Vitrectomy was performed and Fusarium solani infection was confirmed by vitreal culture. The infection was also disseminated to the lung, triceps, and spleen. The splenic lesions disappeared with the administration of antifungal agents, and residual lesions in the lung and triceps were surgically resected. After two courses of consolidation chemotherapy, the patient received cord blood transplantation (CBT) twice because of graft failure in the first transplantation. Antifungal agents were administered continuously during chemotherapy and transplantation. Although Fusarium sinusitis developed after neutrophil engraftment, it was well controlled by surgical resection. Thereafter, the patient has been well without recurrence of fusariosis for more than 2 years since transplantation. A combination of continuous administration of antifungal agents and vigorous surgical intervention may be important for management of disseminated fusariosis in the setting of HSCT.